Zheng He and International Relations: An Asian Cultural Diplomacy Model - Effendi , Tonny Dian (Journal of Integrative International Relations, 2019)
Zheng He is not only an important figure in China’s trade route in Southeast Asia until Africa, but He marked how cultural diplomacy carried out with a peaceful approach. Zheng He journey from China to various countries demonstrated how cultural diplomacy successfully is done. Therefore, the questions are: how is Zheng He diplomacy viewed from diplomacy in international relations study? What are the values that support this succeed? Is it can be a cultural diplomacy model in international relations study, at least for Asian countries? Those questions become the discussion in this article. The argument of this article is Zheng He does not only contribute to bilateral relations between China and the country where he visited, but he contributes in diplomacy study in international relations. Zheng He diplomatic style may become one of Asian diplomacy model, at least it contributes to the history of world diplomacy.